Does releasing foreign investment bounds improve the performance of pension funds? - Chirinos Grados, Miguel Víctor; Universidad Nacional de Colombia (Pontificia Universidad Javeriana, 2015)
This paper evaluates the regulator's proposal to raise the bounds on foreign investment of Peruvians Pension Funds, this elevation improve the PPF´s performance? The issue is analyzed from two perspectives: The first one determines if higher levels of investment in foreign markets improve portfolio diversification; to pin down the degree of correlation we make use of copulas, which provide flexibility in the choice of the univariate series. The second approach analyzes the effect of the shocks generated in foreign markets; for this objective we employ the extreme value theory. Our results suggest, as a policy recommendation, to reduce the levels of both equities and foreign investment in the PF portfolios.